2021
DOI: 10.24908/pceea.vi0.14861
|View full text |Cite
|
Sign up to set email alerts
|

From Understanding to Action: An Examination of Transformative Learning in Asynchronous Online Equity, Diversity, and Inclusion Training for First- Time Teaching Assistants

Abstract: To better support TAs in creating inclusive classrooms, three (3) online, asynchronous modules were developed and implemented to introduce first-time TAs to core concepts of equity, diversity, and inclusion (EDI) - Foundational EDI Language, Power, Privilege, and Positionality and Interrupting Bias. Over 100 1st time TA completed each module, with 80-90 providing feedback on their experience upon completion. A preliminary review of this feedback highlighted three major themes: 1) building awareness and knowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Focusing on organizational differences, such as working with an instructional designer, may introduce faculty to concepts related to equity and inclusivity issues and help them learn about the appropriate teaching approaches to promote the inclusion of students (Hanson & Burke, 2021). Stone et al (2019) examined the experiences of online students in rural settings and found that university policies and processes prevent students from a distance from accessing university services.…”
Section: Inclusion and Equity Differences Framework For Online Learningmentioning
confidence: 99%
“…Focusing on organizational differences, such as working with an instructional designer, may introduce faculty to concepts related to equity and inclusivity issues and help them learn about the appropriate teaching approaches to promote the inclusion of students (Hanson & Burke, 2021). Stone et al (2019) examined the experiences of online students in rural settings and found that university policies and processes prevent students from a distance from accessing university services.…”
Section: Inclusion and Equity Differences Framework For Online Learningmentioning
confidence: 99%